2020
DOI: 10.3389/fpsyg.2020.02049
|View full text |Cite
|
Sign up to set email alerts
|

The College Students’ Sense of Responsibility for Innovation and Entrepreneurship

Abstract: The purpose of this paper is to analyze the relationship between positive psychological quality and college students' sense of responsibility for innovation and entrepreneurship from the perspective of positive psychology, to explore the cultivation model that can effectively improve college students' sense of responsibility for innovation and entrepreneurship, and to promote their success in entrepreneurship. In this study, a total of 1,500 college students were selected for questionnaire survey. ANOVA was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…At present, due to the poor entrepreneurial environment and lame EP, many domestic entrepreneurial enterprises are on the brink of bankruptcy. College entrepreneurs are one of the fundamental forces of entrepreneurship, and under such socio-economic background, the main problem to promote successful entrepreneurship has become improving their EP ( Qian et al, 2018 ; Bronikowska et al, 2020 ; Wu Y. J. et al, 2020 ; Zhang Q. et al, 2020 ). In particular, EP is a crucial enterprise-strength index that reflects how well an enterprise completes a task or achieves a goal in entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…At present, due to the poor entrepreneurial environment and lame EP, many domestic entrepreneurial enterprises are on the brink of bankruptcy. College entrepreneurs are one of the fundamental forces of entrepreneurship, and under such socio-economic background, the main problem to promote successful entrepreneurship has become improving their EP ( Qian et al, 2018 ; Bronikowska et al, 2020 ; Wu Y. J. et al, 2020 ; Zhang Q. et al, 2020 ). In particular, EP is a crucial enterprise-strength index that reflects how well an enterprise completes a task or achieves a goal in entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…However, entrepreneurial intention is the prerequisite for entrepreneurial behavior, and those who have started businesses in the past must take entrepreneurial intention as the guide ( Qiao and Huang, 2019 ). Many researchers indicated that there is a positive relationship between entrepreneurial education and entrepreneurial intention ( Kariv et al, 2019 ; Zhang et al, 2020 ). Another study also confirmed that entrepreneurship education encourages students to pursue entrepreneurship as a career and gives students the skills they need to start a business ( Chen, 2019 ; Marlous et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Educational psychology improves the relationship between entrepreneurial college students, the team and the entrepreneurs, and the external environment. A harmonious and progressive organizational culture and entrepreneurial ecological environment can be established, enhancing the moral responsibility and professional ethics of college entrepreneurs (Zhang et al, 2020 ). While college students' recognition and satisfaction with the entrepreneurial values are improved, their sense of identity and satisfaction with the organization, society, and the nation can be enhanced further.…”
Section: Methodsmentioning
confidence: 99%
“…The results pointed out the developmental direction of fashion entrepreneurship courses based on the perspective of college students in fashion majors. Zhang et al ( 2020 ) examined 668 tourism and hotel majors to explore whether entrepreneurship education would affect students' entrepreneurial intentions. The results found that support education positively impacted entrepreneurial intentions, and practice was the leading factor in forming entrepreneurial intentions, while theoretical improvement was an essential moderating factor.…”
Section: Literature Reviewmentioning
confidence: 99%